1984
DOI: 10.1037/0022-0167.31.4.584
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Self-Directed Search with Native American high school students.

Abstract: This study examined the appropriateness of using the Self-Directed Search (SDS) with Native American Indian high school students. Inventory scores between two different Indian tribes were compared, and then comparisons were made with national normative data. The Native American students differed among themselves on 4 of the 12 scale comparisons, and there were 6 differences on the 24 scale comparisons with the normative groups. The Indian samples showed higher intercorrelational coefficients among the SDS scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Career exploration, personenvironment fit, and goal-setting skills can be taught through providing opportunities for Native American young people to understand their own goals, interests, personalities, and talents and to gather information about the world of work through computer-assisted and print materials. We recommend that counselors use instruments that have been validated on Native American populations, such as the Self-Directed Search (SDS; Gade, Fuqua, & Hurlburt, 1984). This instrument can be particularly effective in that it allows young people to explore their interests in specific activities, their competencies, their occupational preferences, and their self-estimated abilities across the six Holland themes.…”
Section: Discussionmentioning
confidence: 99%
“…Career exploration, personenvironment fit, and goal-setting skills can be taught through providing opportunities for Native American young people to understand their own goals, interests, personalities, and talents and to gather information about the world of work through computer-assisted and print materials. We recommend that counselors use instruments that have been validated on Native American populations, such as the Self-Directed Search (SDS; Gade, Fuqua, & Hurlburt, 1984). This instrument can be particularly effective in that it allows young people to explore their interests in specific activities, their competencies, their occupational preferences, and their self-estimated abilities across the six Holland themes.…”
Section: Discussionmentioning
confidence: 99%
“…They could reflect differences in the environments of different ethnic groups. Some examples of this view are represented by the literature on barriers to career exploration and decision making (McWhirter, 1997;Swanson & Tokar, 1991a,b) and on the lack of role models (Gade, Fuqua, & Hurlburt, 1984;Martin, 1995). Another view is that such mean differences should not exist and that their presence signals a biased instrument (e.g., Carter & Swanson, 1990).…”
Section: Summary and Discussion Of Psychometric Examinationmentioning
confidence: 99%
“…The literature on the occupational choice process has demonstrated that a narrower range of occupations are considered among ethnicracial minority groups (Gottfredson, 1978;Leung, Ivey, & Suzuki, 1994), and some prominent researchers have documented that some of this narrowing can occur as a result of perceptions of barriers in choice options (McWhirter, 1997;Swanson & Tokar, 1991a, 1991b or a lack of models (Gade, Fuqua, & Hurlburt, 1984;Martin, 1995). If this narrowing is true, then ethnic minorThis document is copyrighted by the American Psychological Association or one of its allied publishers.…”
mentioning
confidence: 99%